Quantitative Linguistic Computing with Perl. Fengxiang Fan, Yaochen Deng. - Lei, Lei (Literary & Linguistic Computing, 2012)
The article reviews the book "Quantitative Linguistic Computing with Perl," by Fengxiang Fan and Yaochen Deng.